DATA HANDLING AND PROJECT-BASED LEARNING AT PRIMARY SCHOOL - Papancheva, Rumyana Y (Journal of process management and new technologies, 2017)
The article presents the author’s experience from implementation of project-based learning at Primary school aiming in development of knowledge for data handling. Students conduct variety of surveys and present their results by creative designed diagrams. The work is part of a larger research for developing statistical literacy at Primary school. The project work “Funny diagrams” is described and some conclusions and recommendations are formulated.